(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
The concept of smart city has moved from a technology-driven marketing narrative to an established paradigm in contemporary urban geography and planning. This analysis critically investigates the geographical features of smart city development and how digital infrastructures are transforming urban areas, socio-spatial interactions and governance systems. This study provides a comprehensive geographical framework for comprehending smart cities in terms of urban morphology, spatial justice, digital inequalities and territorial governance through a systematic examination of more than 80 peer-reviewed papers (2015-2026). Three central geographical issues are discussed in the review: first, the development of uneven urban landscapes characterised by differential access and participation through smart city technologies; second, the spatial distribution of digital infrastructures as a reflection and reproduction of existing socio-economic inequalities; and third, the need for place-based approaches sensitive to local cultural, economic and geographic specificities in successful implementation of smart city initiatives. The study finishes with a discussion of key objectives for future research in geography on smart urbanism, including the importance of comparative spatial analysis, a focus on ordinary urban experiences and the convergence of sustainability and justice agendas.